Twists and Turns : New Business Models - Graham, John (International Finance Corporation, Washington, DC, 2020)
Electric buses have been the fastest-growing electric vehicle segment over the past five years by a wide margin. The market is changing quickly as both national and local governments make new commitments to address climate change and the horrific air quality conditions that plague some cities. To convert these ambitious commitments into reality, there is need of investable and bankable business models that work on a standalone basis. The state-heavy model, complete with lavish subsidies, won’t work for developing countries. So, the marketplace needs to invent the wheel here. Based on the early work on electric vehicles, what are some of the business models taking shape are presented in the report.